2020
DOI: 10.1507/endocrj.ej19-0276
|View full text |Cite
|
Sign up to set email alerts
|

Insulin induces expression of the hepatic <i>vaspin</i> gene

Abstract: Visceral adipose tissue-derived serine protease inhibitor (vaspin), initially identified in the visceral adipose tissue, is an adipokine that improves endoplasmic reticulum stress in obesity or insulin sensitivity and glucose tolerance. However, the transcriptional regulation of the hepatic vaspin gene remains elusive. We have previously shown that CCAAT-enhancerbinding protein α, a transcription factor of the basic leucine zipper class, positively regulates the vaspin gene. The present study aimed to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…We observed that expression of diverse types of genes is altered by lacking Hvcn1 (Tables 1 and 2). It is interesting that we observed the drastic expression change of Hcn3 and Serpina12 that have close relationship with diabetes 25,26 . It is possible that this expression change was caused by the alteration of glucose level that is observed both in the previous and the present studies.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We observed that expression of diverse types of genes is altered by lacking Hvcn1 (Tables 1 and 2). It is interesting that we observed the drastic expression change of Hcn3 and Serpina12 that have close relationship with diabetes 25,26 . It is possible that this expression change was caused by the alteration of glucose level that is observed both in the previous and the present studies.…”
Section: Discussionsupporting
confidence: 73%
“…It is interesting that we observed the drastic expression change of Hcn3 and Serpina12 that have close relationship with diabetes. 25,26 It is possible that this expression change was caused by the alteration of glucose level that is observed both in the previous and the present studies. On the contrary, it appears that the influence of these genes on Hvcn1-deficient liver function is limited, because the basic expression level of these genes is quite low (Table 1), and therefore, their function has not been established in liver.…”
Section: Hv1/vsop Suppresses Ros Production In Kupffer Cellssupporting
confidence: 53%
“…On the other hand, the result of an experimental study in mice reported that injection of insulin in fasting status increase the hepatic expression of vaspin [31]. Previous studies have indicated that serum concentration of vaspin was increased with worsening insulin resistance in children and impaired glucose tolerance and obesity in adults [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the results of experimental study in mice, reported that injection of insulin in fasting status increased positively the hepatic expression of vaspin [30].…”
Section: Discussionmentioning
confidence: 96%